Right Ventricular Strain before and after Pulmonary Thromboendarterectomy in Patients with Chronic Thromboembolic Pulmonary Hypertension. Issue 7 (18th October 2014) - Marston, Nicholas; Brown, Jason P.; Olson, Nicholas; Auger, William R.; Madani, Michael M.; Wong, Darrin; Raisinghani, Ajit B.; DeMaria, Anthony N.; Blanchard, Daniel G.
<x xml:space="preserve">Abstract</x> Background Right ventricular (RV) function is significantly impaired in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Two‐dimensional speckle tracking RV strain and strain rate are novel methods to assess regional RV systolic function in CTEPH patients before and after pulmonary thromboendarterectomy (PTE). Our goal was to (1) assess baseline longitudinal strain and strain rate of the basal RV free wall in CTEPH and (2) measure early changes in RV strain and strain rate after PTE. Methods We performed echocardiography on 30 consecutive patients with CTEPH referred for PTE with adequate pre‐ and post‐PTE strain imaging. Strain and strain rate were assessed 6.4 ± 4.5 days before and 9.1 ± 3.9 after PTE. Results Basal RV free wall strain and time to peak strain—but not basal RV strain rate and time to peak strain rate—changed significantly after PTE. Unexpectedly, basal RV strain became less negative, from −24.3% to −18.9% after PTE (P = 0.005). Time to peak strain decreased from 356 to 287 msec after PTE (P < 0.001). Preoperatively, RV strain correlated with pulmonary vascular resistance (PVR) and mean pulmonary artery pressure (mPAP) but this relationship was not evident postoperatively. Furthermore, the change in RV strain did not correlate with the change in mPAP or PVR. Conclusions In patients with CTEPH, RV basal strain paradoxically became less negative (i.e., relative systolic shortening decreased) following PTE. This change in RV strain could be due to intraoperative RV ischemia and/or postoperative stunning. Thus, RV basal strain cannot be used as a surrogate marker for surgical success early after PTE.